Enhancing Teacher Professionalism through the Development of a PositiveSelf-Concept Based on Communication Psychology - Nurwahyuni, Nurwahyuni; ZA, Tabrani (SCAD Independent, 2025)
This study examines how teacher professionalism can be effectively enhanced through the development of a positive self-concept using a communication psychology approach. Conducted at SMP Negeri Kota Banda Aceh, the research addresses long-standing challenges related to low teacher motivation, seniority-based hierarchies, limited ICT competence, and weak collaboration between civil servant teachers (PNS) and non-permanent teachers (GTT). Using a qualitative design, data were collected through observations, interviews, and documentation over a six-month intervention period focusing on interpersonal communication, small-group communication within MGMP meetings, and large-group communication led by the school principal. The findings show that communication psychology significantly improves teachers’ confidence, motivation, and willingness to engage in professional tasks. Teachers demonstrated increased digital competence, greater openness to collaboration, stronger reflective practices, and improved pedagogical initiative. The intervention also helped reduce social gaps between PNS and GTT teachers by fostering a more supportive relational climate. These results suggest that teacher professionalism is not solely a technical or administrative issue but a psychosocial construct shaped by relational support, communication patterns, and emotional validation. The study concludes that communication-based interventions can serve as effective strategies for professional development in schools with hierarchical cultures. Future research should employ longitudinal or mixed-method designs to examine sustainability and broader applicability.